An Abstract Machine for the Stochastic Bioambient Calculus - Phillips, Andrew (Electronic Notes in Theoretical Computer Science, 2009)
This paper presents an abstract machine for the stochastic bioambient calculus. The abstract machine is proved sound and complete with respect to a novel stochastic semantics, and is also shown to preserve the reduction probabilities of the calculus. The machine is implemented as an extension to an existing simulator for stochastic pi-calculus.